Synthesis and biological testing of 5-methyl-2'-deoxycytidine analogues and Perfluoroalkylation reactions of amines - Scollan, Alexander (2021)
Chapter one describes efficient syntheses of an array of 5-methyl-2’-deoxycytidine nucleoside analogues, designed to target the TET family of enzymes. Prepared compounds were tested on a cytotoxicity assay against several different cell lines and a highly toxic difluorinated compound was discovered. One compound was additionally prepared in the phosphoramidite form for solid phase DNA synthesis.